Investigating users' perspectives on the development of bike-sharing in Shanghai. (September 2021) - Lyu, Yinxue; Cao, Mengqiu; Zhang, Yuerong; Yang, Tianren; Shi, Cheng
Abstract: High levels of car dependence have caused tremendous challenges for sustainable transport development. Transport planners, therefore, seek ways of replacing motor vehicles, as well as increasing the proportion of active travel. The bike-sharing scheme can be seen as an effective way of doing so, particularly in Asian cities. The aim of this paper is to investigate users' perspectives on the development of bike-sharing using Shanghai as an example. Semi-structured interviews are used to examine the main factors motivating and impeding the development of the bike-sharing scheme in Shanghai. Our findings show that convenience, saving time and financial savings are the major motivations; whereas problems with bicycles being poorly maintained and abused by users, operational issues, financial issues and an unsuitable business model are the major obstacles. In addition, the findings also suggest that a public and private partnership could be the best option for running a sustainable bike-sharing scheme with clear areas of responsibility. Financial incentives, a bicycle-friendly infrastructure, regular operational management and supportive policies should be prioritised. In order to achieve the targets set by the Shanghai Master Plan 2035, transport planners and policymakers should integrate the bike-sharing scheme within the wider active travel system. Highlights: Convenience, saving time and financial savings are the major reasons motivating people to use shared bicycles. Problems with bicycles being poorly maintained and abused by users, and operational issues are the major obstacles. A public and private partnership could be the best option for running a sustainable bike-sharing scheme. Financial incentives, a bicycle-friendly infrastructure and supportive policies should be prioritised.